Análise da disponibilidade hídrica utilizando modelo de dinâmica de sistemas no município de Araraquara-SP - Galvão, Helton Alves de (2024)
Population growth and urbanization have brought more complex challenges to the management of cities and water resources. The frequency with which new water crises emerge shows that the problem is not exclusive to large urban agglomerations, nor to regions with historical scarcity problems. In Brazil, at the national level, the relationship between water availability and demand does not indicate scenarios of stress or scarcity, but when the issue is addressed at the regional or local level, there are scenarios that are more susceptible to this condition. This means that decision-making on water resources requires a better understanding of local and regional contexts, as well as the ability to estimate future water availability scenarios with a greater degree of certainty. In this way, this research aims to analyze water availability in the municipality of Araraquara-SP, considering a local approach to the relationship between demands and the dynamics of land use and occupation. To this end, a systematic literature review and documentary research on the study area were conducted, and a conceptual model using system dynamics was developed to analyze water availability in the community. The main relationships established in the model were based on the local water supply, variations in demand and type of water use, population growth, and variations in land use and occupation, both urban and rural. For the simulated scenarios, a progressive reduction in the rate of water loss in the urban supply system and a reduction in per capita demand in the urban area were considered as intervention measures for water availability. The results obtained were positive and demonstrated the viability of these actions to improve water availability in the municipality in the medium and long term. Finally, the feasibility of using system dynamics as a method for analyzing water availability in a local context and dynamic modeling as a management tool for analyzing water availability at the municipal level was verified.